2018
DOI: 10.1016/j.joca.2018.02.899
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind placebo-controlled crossover trial of HUMira (adalimumab) for erosive hand OsteoaRthritis – the HUMOR trial

Abstract: ACTRN12612000791831.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 24 publications
2
80
0
3
Order By: Relevance
“…However, studies of adalimumab have not shown it to be effective compared to placebo in reducing symptoms of hand OA [83,84]. More recently, the HUMOR trial compared subcutaneous adalimumab 40 mg on alternative weeks versus placebo over 12 weeks in a crossover-design study of 43 patients with erosive hand OA and synovitis seen on magnetic resonance imaging (MRI) [85]. There was an 8-week washout period before treatment groups crossed over.…”
Section: Tumour Necrosis Factor Inhibitorsmentioning
confidence: 99%
“…However, studies of adalimumab have not shown it to be effective compared to placebo in reducing symptoms of hand OA [83,84]. More recently, the HUMOR trial compared subcutaneous adalimumab 40 mg on alternative weeks versus placebo over 12 weeks in a crossover-design study of 43 patients with erosive hand OA and synovitis seen on magnetic resonance imaging (MRI) [85]. There was an 8-week washout period before treatment groups crossed over.…”
Section: Tumour Necrosis Factor Inhibitorsmentioning
confidence: 99%
“…102 Currently, no DMOADs have been licensed for use in the treatment of OA, but several putative DMOADs are in phase II development. In particular, monoclonal antibodies (mAbs) and inhibitors directed against OA-related cytokines, such as tumor necrosis factor α (TNF-α), [103][104][105][106] nerve growth factor, [107][108][109] or interleukin molecules like IL-1α/β, [110][111][112] are under investigation, due to their regular use as biological disease-modifying antirheumatic drugs (bDMARDs) for the management of rheumatoid arthritis inflammation. 113 In a report comparing safety outcomes of bDMARDs in rheumatoid arthritis in 42 observational studies, a general safety profile of bDMARDs emerged with very sporadic cases of cardiovascular and infection incidence.…”
Section: Monoclonalmentioning
confidence: 99%
“…Another example is the TNF-α inhibitor etanercept (Enbrel ® ) which was the first biopharmaceutical on the market approved by U.S. F.D.A to treats chronic autoimmune and inflammatory diseases such as rheumatoid arthritis, juvenile rheumatoid arthritis and psoriatic arthritis (Rider et al, 2016). A further example is, Adalimumab (Humira ® ), a fully human monoclonal antibody against TNF-α, that can relieve symptoms of autoimmune diseases, reduce inflammation and inhibit chronic pain (Aitken et al, 2018). The TNF-α inhibitors, certolizumab and golimumab, were also approved for the treatment of rheumatoid arthritis, psoriatic arthritis, and Crohn's disease unresponsive to regular medications (Rider et al, 2016).…”
Section: Cytokines As Targets For the Development Of Drugsmentioning
confidence: 99%